Isolation of a bioemulsifier from Candida lipolytica. - Cirigliano, M C (1984)
The yeast Candida lipolytica produced an inducible extracellular emulsification activity when it was grown with a number of water-immiscible carbon substrates. Negligible emulsification activity was produced by this yeast when it was grown with glucose as the carbon substrate. In hexadecane-supplemented cultures, emulsification activity was first detected after 36 h of growth, with maximum production after 130 h. A water-soluble emulsification activity was partially purified by repeated solvent extractions of the culture filtrate. This emulsifier, which we named liposan, was primarily composed of carbohydrate. Maximum emulsification activity was obtained when the ratio of hexadecane to liposan was 50:1. Maximum emulsification activity was obtained from pH 2 to 5. Liposan was heat stable to temperatures up to 70 degrees C, with a 60% loss in activity after heating for 1 h at 100 degrees C. Liposan effected stable oil-in-water emulsions with a variety of hydrocarbons.